2023
DOI: 10.1155/2023/9398167
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Study and Removal of Basic Fuchsin Dye from Medical Laboratory Wastewater Using Local Natural Clay

Abstract: Local natural clay from Sulaimani zone-Takiya (TKC), Kurdistan Region of Iraq, was characterized and used for the removal of basic fuchsin (BF) dye from laboratory bacterial wastewater. The characterization of the adsorbent was carried out with XRD, XRF, and FT-IR. The clay sample was dominated by vermiculite. Adsorption tests under different conditions of contact time, pH of the solution, temperature, initial dye concentration, and adsorbent amount were performed to analyze the effect of various experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It was found that the uptake efficacy of BFD dye decreased, whereas the uptake capability of the KE, KE500, and KE700 adsorbents increased with increasing initial dye concentrations. The Langmuir (Equation ( 5)) in addition to the Freundlich (Equation ( 6)) equilibrium equations [16,[37][38][39][40] were operated to study the linear fitting of the obtained experimental data owing to the disposal of BFD dye by the KE, KE500, and KE700 products, as displayed in Figure 14A,B, respectively.…”
Section: Effect Of Interaction Timementioning
confidence: 99%
“…It was found that the uptake efficacy of BFD dye decreased, whereas the uptake capability of the KE, KE500, and KE700 adsorbents increased with increasing initial dye concentrations. The Langmuir (Equation ( 5)) in addition to the Freundlich (Equation ( 6)) equilibrium equations [16,[37][38][39][40] were operated to study the linear fitting of the obtained experimental data owing to the disposal of BFD dye by the KE, KE500, and KE700 products, as displayed in Figure 14A,B, respectively.…”
Section: Effect Of Interaction Timementioning
confidence: 99%
“…The parameters that affected the adsorption such as pH, contact time, temperature, adsorbent dose, and initial dye concentration were determined. The maximum amount of dye adsorbed is about 149.2 mg g −1 or 0.44 mmol g −1 26 …”
Section: Introductionmentioning
confidence: 99%
“…The maximum amount of dye adsorbed is about 149.2 mg g −1 or 0.44 mmol g −1 . 26 The present paper examined the feasibility of using HAP to remove BF from aqueous solution. The effect of various operational parameters, such as PS concentration, solution pH, and temperature on the discoloration efficiency of (BF) dye, was investigated.…”
Section: Introductionmentioning
confidence: 99%